Inovasi Dan Digitalisasi Sebagai Kunci Daya Saing Umkm Indonesia Di Pasar Global - Andita, Khalisa Putri; Chalista Aurelia Cherit; Ellena Shinta (GLOBAL SCIENTS PUBLISHER, 2025)
Global economic dynamics and rapid digital technological advancement require Indonesian Micro, Small, and Medium Enterprises (MSMEs) to adapt in order to remain competitive in international markets. Innovation and digitalization are considered strategic factors that can enhance MSMEs’ competitiveness through market expansion, operational efficiency, and improved product and service quality. This study aims to analyze the role of innovation and digitalization as key drivers of Indonesian MSMEs’ competitiveness in the global market. The research employs a qualitative approach using a literature review method, with secondary data obtained from scientific journal articles, research reports, and relevant academic publications. Data analysis is conducted through content analysis to identify patterns, relationships, and strategic implications from previous studies. The findings indicate that digitalization, particularly through the utilization of e-commerce platforms, social media, and digital payment systems, significantly improves MSMEs’ market access and business efficiency. Furthermore, product and business model innovation supported by digital technology strengthens MSMEs’ competitive position in the global market. However, challenges such as limited digital literacy, financial constraints, and inadequate technological infrastructure remain obstacles to effective implementation. Therefore, collaboration among MSMEs, government, and relevant stakeholders is essential to support sustainable digital transformation.